Nutritional management of a malnourished cancer patient with high output ileostomy: A case Report - Adelina Haryono; Diana Sunardi; Wina Sinaga (Indonesian Nutrition Association, 2023)
High output stoma is a complication that may follow ileostomy formation, with an incidence of 23%. There is no general consensus on the limit of ileostomy production to be defined as high output. However, output of more than 2000 mL/day, can cause fluid and electrolyte imbalance, also malnutrition due to reduced nutrient absorption. Delay in recognition and treatment, especially in cancer patient with high risk of malnutrition, can further deteriorate patient’s nutritional status. A 43-year-old malnourished female with ascending colon cancer underwent tumor resection and ileocolostomy surgery. Starting from the third postoperative day, ileostomy effluent drastically increased to 2700 mL/day, causing severe hyponatremia, hypokalemia, and hypomagnesemia. Risk factors of high output stoma identified were routine prokinetic medication use and unresolved malignancy-related retroperitoneal abscess. Moreover, increment of food intake in the first days after surgery, specifically food high in insoluble fiber, was one of the contributing factors. High output stoma was then resolved by abscess drainage, discontinuation of prokinetic agent, and administration of antimotility agent. Hyponatremia and hypomagnesemia improved with correction, whereas hypokalemia needed longer time to resolve. Enteral nutrition was maintained and increased gradually to prevent further malnutrition. Oral hypotonic fluid intake was limited to 1000 mL/day and isotonic solution consumption was advised. High stoma production due to hypersecretory phase after ileostomy was expected, but thorough management would prevent patient’s deterioration that was caused by the fluid, electrolyte, and nutritional imbalances.